Transformasi Digital dan Moderasi Beragama: Memperkuat Ummatan Wasathan di Indonesia - Adi Fadli (Schemata: Jurnal Pascasarjana UIN Mataram, 2023)
This study uses the literature review method (Library Research) to collect data from relevant literature, such as scientific journals, books, magazines, and other documents. This study focuses on a content study approach to analyze data in detail based on print media and informatics media such as ebooks. The results of the study show that digital transformation has a significant influence on people's mindsets and behavior in the context of religious moderation in Indonesia. The development of digital technology, such as the internet, social media, and online communication platforms, has changed the way people interact, access information, and form religious identities. However, digital transformation also carries risks in the context of religious moderation. The spread of extremist and provocative content on online platforms can influence people's mindsets and behavior. In the Indonesian context, digital transformation also opens up opportunities for preachers, especially young people, to disseminate da'wah content digitally. The government, educational institutions, religious communities and social media platforms need to work together to strengthen religious moderation in the digital era. Therefore, digital transformation has a complex impact on religious moderation in Indonesia. With good social media literacy and digital literacy, as well as collaborative efforts between various parties, it is hoped that religious moderation can be strengthened in facing challenges and taking advantage of the opportunities offered by the digital era Keywords: Digital Transformation, Religious Moderation, Ummatan Wasathan Penelitian ini menggunakan pendekatan kualitatif dengan metode kajian pustaka (Library Research) untuk mengumpulkan data dari literatur yang relevan, seperti jurnal ilmiah, buku, majalah, dan dokumen lainnya. Penelitian ini memfokuskan pada pendekatan kajian isi untuk menganalisis data secara mendetail berdasarkan media cetak dan media informatika seperti ebook. Hasil penelitian menunjukkan bahwa transformasi digital memiliki pengaruh yang signifikan terhadap pola pikir dan perilaku masyarakat dalam konteks moderasi beragama di Indonesia. Perkembangan teknologi digital, seperti internet, media sosial, dan platform komunikasi online, telah mengubah cara masyarakat berinteraksi, mengakses informasi, dan membentuk identitas keagamaan. Namun, transformasi digital juga membawa risiko dalam konteks moderasi beragama. Penyebaran konten ekstremis dan provokatif di platform online dapat mempengaruhi pola pikir dan perilaku masyarakat. Dalam konteks Indonesia, transformasi digital juga membuka peluang bagi para pendakwah, terutama dari kalangan pemuda, untuk menyebarkan konten dakwah secara digital. Pemerintah, lembaga pendidikan, komunitas agama, dan platform media sosial perlu bekerja sama dalam memperkuat moderasi beragama di era digital. Oleh kerena itu,  transformasi digital memiliki dampak kompleks terhadap moderasi beragama di Indonesia. Dengan literasi media sosial dan literasi digital yang baik, serta upaya kolaboratif antara berbagai pihak, diharapkan moderasi beragama dapat diperkuat dalam menghadapi tantangan dan memanfaatkan peluang yang ditawarkan oleh era digital. Kata kunci: Transformasi Digital, Moderasi Beragama Ummatan Wasathan